Spatiotemporal bycatch analysis of the Atlantic halibut (Hippoglossus hippoglossus) longline fishery survey indicates hotspots for species of conservation concern. Issue 1 (12th April 2019) - Hurley, Isabelle; Wringe, Brendan F.; den Heyer, Cornelia E.; Shackell, Nancy L.; Lotze, Heike K.
Abstract : The Atlantic halibut ( Hippoglossus hippoglossus ) longline fishery is the second most valuable groundfish fishery in Atlantic Canada and received Marine Stewardship Council certification in 2013. The bottom longline fishery accounts for most halibut landings but incidentally catches nontargeted species (bycatch). Since 1998, Fisheries and Oceans Canada and the halibut fishing industry performed annual longline surveys across the Scotian Shelf and Southern Grand Banks stock management area to monitor halibut abundance, and at‐sea observers also recorded bycatch information. We examined the species composition and proportion of the survey bycatch and analyzed temporal and spatial trends in standardized weight of (a) halibut catch, (b) total bycatch, and (c) bycatch of species of conservation concern. From 1998 to 2016, 70% of the total catch by weight and 85% by number of individuals were bycatch. Over 100 identified species of finfish, sharks, skates, benthic invertebrates, marine mammals, and seabirds were caught as bycatch in the survey. This included four species listed under the Species at Risk Act (Northern wolffish, Anarhichas denticulatus ; spotted wolffish, A. minor ; Atlantic wolffish, A. lupus; Atlantic cod, Gadus morhua ), and another 14 species awaiting a listing decision based on assessments by the Committee on the Status of Endangered Wildlife in Canada. Generally, the standardized weight of halibut and barndoor skate ( Dipturus laevis ) increased over time, while Atlantic cod, spiny dogfish ( Squalus acanthias ), white hake ( Urophycis tenuis ), and thorny skate ( Amblyraja radiata ) decreased. Spatial patterns indicated high bycatch levels on the southern Scotian Shelf and southern edge of the Southern Grand Banks, with hotspots for certain species of conservation concern. Our results identify temporal trends in threatened species and areas where they are susceptible to the Atlantic halibut longline fishery which can inform recovery strategies, bycatch levels and spatial zoning in fisheries management and marine conservation.